Subaortic Membrane Late after Surgical Correction of Tetralogy of Fallot - Kim, Kyung-Hee (The Korean Association of Internal Medicine, 2012)
We herein report a rare case of subaortic stenosis in association with a previous tetralogy of Fallot (TOF) surgical repair, which was not taken into account as a differential diagnosis. Echocardiography plays a pivotal role in identification of this rare combination. Therefore, echocardiography should be performed periodically during follow-up of patients with surgically corrected TOF. Given the clinical complications that can result from subaortic stenosis (i.e., aortic regurgitation and infective endocarditis), early and aggressive management of this rare combination should be performed.